Pengembangan Citra Merek sebagai Identitas Merek “Arak Besan” dalam Menghadapi Kompetitor - Nyoman Sri Subawa; Ni Wayan Widhiasthini; Ni Putu Intan Permatasari; Ni Nyoman Sri Wisudawati (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: provide training and understanding of the importance of brands in product development and marketing. Method: Training and counseling for "Arak" beverage craftsmen, on a scheduled and programmed basis in Besan Village, as one of the "Arak" beverages producing villages. Result: The community and the "Arak" beverage craftsmen, have understood the importance of brands in marketing and distributing products as product identities and are able to compete with competitors, producers of similar products. Limitation: Limitations in cost and scope of training are limited to one village, so counseling and training are needed for "Arak" drink craftsmen in other villages. Education needs to be carried out on an ongoing basis. Contribution: This form of training, mentoring, and counseling provides benefits to the craftsmen and the “Arak” beverage community, the importance of brands in facing competition in the beverage business.